Object Biography of a Series of Radioactive Drill Cores from Shinkolobwe, Democratic Republic of Congo - Livia Cahn (Museum & Society)
This object biography takes as its starting point a radioactive drill core encountered in a collection of geological samples in the Democratic Republic of Congo. Departing from a double blindness of not having seen the core and not being able to see its radioactivity, significant connections are drawn out between where the core is stored and the colonial context it was extracted from. This relation is further complicated by focusing on the mineral extraction it informed, what the mineral extracted it informed was used for, and the fate of the stored core. The biography of the mineral sample is furthermore pieced together by consulting related paper archives and addressing wider social and environmental effects.